AB0585 SINGLE CENTER EXPERIENCE OF CLINICAL PROFILE OF INFLAMMATORY MYOSITIS FROM INDIA. (2nd June 2020) - Kulkarni, N.; Venugopalan, A.; Saluja, M.; Chopra, A.
Abstract : Background: Clinical profile of myositis differs in respect of the setting. We present a single center experience from a community based referral center Objectives: STUDY CLINICAL PROFILE OF INFLAMMATORY MYOSITIS (IM) Methods: We present data from 114 patients of connective tissue disorders (CTD) with dominant Inflammatory Myopathy(IM) evaluated in CRD where we have patient database since 1996. Standard investigations & ELISA, immunoblot and nephlometry to assay autoantibodies (AAb) were done. Data extraction done from 2005-2017 Results: 36 and 28 patients respectively diagnosed as dominant idiopathic dematomyositis (DM) and polymyositis (PM); remaining 41 patients showed overlap (OCTD). Mean onset age range 33-40 years in each subset with women dominance. Exclusive proximal muscle involvement seen 64% DM, 67% PM and 43% OCTD. 12 of OCTD showed classical DM rash. Raynauds's phenomenon was seen in 38% (25% DM, 10% PM, 65% OCTD). 83% OCTD showed inflammatory polyarthritis; DM 29% and PM 42%. Two patients DM also diagnosed malignancy (ovarian CA). 25% DM, nil PM and 31.7% OCTD showed CT based lung findings. Mean creatinine phosphokinase at diagnosis were DM 1580, PM 2239 & OCTD 830. EMG required in 48 patients confirmed diagnosis (DM 17, PM 16 and OCTD 15). Seven patients with diagnostic dilemma/ poor therapy response required muscle histopathology confirmation. 59% DM, 69% PM and 84% OCTD were seropositive ANA positive in 71%(ENA profile available for most). All Patients received steroids. Methotrexate prescribed in (92%), Azthioprine in (28%), hydroxychloroquine in (88%) with majority showing good response. Mycophenolate prescribed in (6%) for aggressive disease, IVIG in 2 patients for acute IIM with interstitial pneumonitis. Rituximab was prescribed in 4 resistant cases; all responding favourably. Mortality data of 4 patients(severe myositis(1), interstitial pneumonitis(1), ovarian cancer(1), septic shock(1)) was available. Antesynthatase syndrome noted in 9 patients. Conclusion: Overlap CTD with myositis seems more common profile than DM or PM. Response to therapy was satisfactory with steroids and methotrexate being the mainstay. Rituximab is a promising biological agent in chronic resistant cases. References: [1]A Kumar. Idiopathic Inflammatory Myopathies. Suppliment to JAPI, JUNE 2006, VOL. 54; Pg 62-66 [2]R Porkodi et al Clinical Spectrum of Inflammatory Myositis in South India - A Ten Year Study. J Assoc Physicians India 2002;50:1255-1258 [3]Chowdhary V, Aggarwal A, Misra R. Prevalence and clinical association of myositis-specific autoantibodies in North Indian patients with idiopathic inflammatory myopathy. APLAR J Rheumatol 2 001. Acknowledgments: STAFF AND PATIENTS OF CENTER FOR RHEUMATIC DISEASES, PUNE Disclosure of Interests: NACHIKET KULKARNI Speakers bureau: PFIZER, NOVARTIS, YANSEN, Anuradha Venugopalan: None declared, MANJIT SALUJA: None declared, Arvind Chopra Grant/research support from: Zydus Pharamceutical Ltd India